Outcome of biological therapies in chronic antibiotic-refractory pouchitis: A retrospective single-centre experience. Issue 9 (November 2019) - Verstockt, Bram; Claeys, Charlotte; De Hertogh, Gert; Van Assche, Gert; Wolthuis, Albert; D'Hoore, André; Vermeire, Séverine; Ferrante, Marc
Background: In limited retrospective series, infliximab, adalimumab and vedolizumab have demonstrated efficacy in chronic antibiotic-refractory pouchitis. Here, we report single-centre data of all biological therapies in refractory pouchitis. Methods: We retrospectively assessed all records from patients with ulcerative colitis and ileal pouch -anal anastomosis who received infliximab, adalimumab or vedolizumab for pouchitis. Clinically relevant remission, defined as a modified Pouchitis Disease Activity Index <5 and a reduction of modified Pouchitis Disease Activity Index ≥2 points from baseline, was assessed at week 14. Results: Thirty-three unique patients were identified. Prior to colectomy, patients had been exposed to cyclosporine ( n = 14), infliximab ( n = 12), adalimumab ( n = 3), and/or vedolizumab ( n = 3). All developed chronic antibiotic-refractory pouchitis, for which they received infliximab ( n = 23), adalimumab ( n = 13) or vedolizumab ( n = 15). Clinically relevant remission was observed in 43.5% of patients in the infliximab group, and in 38.5% and 60.0% in the adalimumab and vedolizumab group, respectively. In the long-term, significantly more patients continued vedolizumab compared to anti-tumour necrosis factor (anti-TNF) therapy (hazard ratio 3.0, p = 0.04). Adverse events (mainly infusion reactions) explained 40.7% of the patients discontinuing anti-TNF therapy, whereas discontinuation of vedolizumab was only related to insufficient efficacy. Four patients eventually required a permanent ileostomy. Conclusion: In this case series of chronic antibiotic-refractory pouchitis, biological therapy was effective in the majority of patients and only a minority eventually required a permanent ileostomy. The use of anti-TNF agents was hampered by a high rate of adverse events, partly related to immunogenicity as some patients had been exposed to anti-TNF prior to colectomy. Vedolizumab was also efficacious and may provide a safe alternative in these chronic antibiotic-refractory pouchitis patients.